Translation to Portuguese and validation of the Diabetes Quality of Life Measure (DQOL-Brazil) - Correr, Cassyano Januario (2015)
Objective: To evaluate the psychometric properties of Brazilian version of Diabetes Quality of Life measure (DQoL-Brazil). Methods: The DQOL was translate to Portuguese, following a recommended protocol, and applied to 121 subjects (56.2% females) with average diagnostic to type 2 diabetes of 8.1 (SD=7.13) years, (range 32-89 years old). Results: The translated measure showed high internal consistency (Cronbach's alpha = 0.92). A positive correlation (p 0.01) was found between all the items and their scales and the total score of instrument, except in the items 18 and 35. These items were excluded from the translated version of DQoL. In concurrent validity analysis, patients with HbA1C higher than 9% presented a significantly higher (p